Intercomparison of personal and ambient dosimeters in extremely high-dose-rate pulsed photon fields. (July 2020) - Zorloni, Gabriele; Ambrožová, Iva; Carbonez, Pierre; Caresana, Marco; Ebert, Stephan; Olšovcová, Veronika; Pitzschke, Andreas; Ploc, Ondrej; Pozzi, Fabio; Silari, Marco; Trompier, Francois; Trunecek, Roman; et al.
Abstract: Recent advances in laser driven accelerators boosted the development of high dose-rate fast pulsed systems all over the world. The stray radiation comprises primarily high-energy photons, resulting in extremely high dose rates within pico-/femto-second pulses. Dose measurements in such conditions have to be evaluated to validate methods. To tackle this challenge the EUropean RAdiation DOSimetry Group (EURADOS) started a program of dosimeters intercomparison, with a progressive approach, starting by a first evaluation in fields with μs pulse duration. The first comparison took place at the Lausanne University Hospital Center with an electron LINAC in Sept. 2017 involving 7 European institutes. Several passive and active dosimeters were tested with a tunable air kerma per pulse of the order of MGy/h. All instruments, except electrets, did not show any dose rate dependence, thus being selected as possible candidates for further studies. Highlights: Laser driven accelerators spread out worldwide. Pulsed accelerator facilities brought with them high dose rate pulsed stray fields. Traditional dosimeters and methods require new tests in new pulsed environments. Intercomparisons are valuable tools for testing instruments and methods together. EURADOS promoted a first dosimeter intercomparison in a pulsed field.